2022
DOI: 10.3390/land11040541
|View full text |Cite
|
Sign up to set email alerts
|

Soil Aggregate Stability in Salt-Affected Vineyards: Depth-Wise Variability Analysis

Abstract: Soil aggregate stability is an ideal integrative soil quality indicator, but little is known about the relevance of such an indicator with soil depth for salt-affected soils. The objective of this study was to determine soil aggregate stability and identify preponderant aggregation factors, both in topsoil and subsoil horizons in salt-affected conditions. We conducted field investigations by describing soil profiles in pedological pits and by collecting soil samples from different field units. Soils were sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…From the mean value of both surfaces, it was revealed that the the lowest value (25%) was recorded in Bhawarna, whereas the highest (56%) was recorded in Narghota, Higher water stable aggregates in soils might be due to higher organic matter content and enhanced microbial activity which secretes binding material during the decomposition process, giving rise to better structure and stable aggregates. The results were in consonance with the findings of Bless et al (2022) and Baker et al (2004).…”
Section: Resultssupporting
confidence: 90%
“…From the mean value of both surfaces, it was revealed that the the lowest value (25%) was recorded in Bhawarna, whereas the highest (56%) was recorded in Narghota, Higher water stable aggregates in soils might be due to higher organic matter content and enhanced microbial activity which secretes binding material during the decomposition process, giving rise to better structure and stable aggregates. The results were in consonance with the findings of Bless et al (2022) and Baker et al (2004).…”
Section: Resultssupporting
confidence: 90%
“…These results fall in line with findings of (Li et al, 2020) who found the same trend. These results could be due to soil salinity which increase aggregates of particles and decrease soil bulk density (Bless et al, 2022). F1 36.26 8.26 309.43 35.26 7.86 311.16 F2 41.16 12.17 321.33 41.25 11.83 331.66 F3 38.96 10.31 318.56 37.50 10.15 329.66 F4 33.38 9.85 303.66 31.66 9.07 309.33 F5 28.71 7.37 289.63 27.60 8.03 296.66 W2 F0 48.96 14.02 343.66 44.67 13.00 348.66 F1 35.5 10.84 318.33 34.53 10.19 324.43 F2 27.85 7.77 309.33 26.26 7.71 311.53 F3 28.70 8.91 313.00 27.20 8.25 313.83 F4 41.15 11.76 323.83 40.56 11.39 325.33 F5 43.06 12.06 335.80 41.56 11.79 336.00 W3 F0 55.15 13.50 376.66 52.75 13.10 377.00 F1 40.41 11.98 353.90 39.71 11.86 358.33 F2 28.95 8.90 347.33 27.57 8.86 348.33 F3 32.87 10.32 350.33 31.53 10.50 351.00 F4 46.92 12.05 360.86 44.85 12.13 370.33 F5 48.24 12.63 364.76 45.86 13.06 383.00 LSD at 0.05 2.0829 0.3908 2.0396 0.5892 0.5026 2.7474 W1= 0.5 dsm -1 , W2= 2.25 dsm -1 , W3= 5.7 dsm -1 F0= without compost, F1= compost applied to soil, f2= compost +foliat potassium silicate F3= compost + coated tuber with potassium silicate, f4= compost + foliar potassium humate, f5= compost +coated tuber with potassium humate…”
Section: Effect Of Different Treatments On N P and K Uptakes In Tuber...mentioning
confidence: 99%
“…However, two additional factors that can affect aggregate formation, thus aggregate stability, are soil sodium concentration and/or salinity in general. A relatively large sodium concentration can cause clay dispersion and destabilize soil aggregates [9] [10]. Clay particles dispersed by elevated sodium can clog inter-aggregate pores, which, in turn, can reduce surface and sub-surface soil hydraulic conductivity and internal drainage and potentially increase surface runoff and erosion [5].…”
Section: Introductionmentioning
confidence: 99%
“…Clay particles dispersed by elevated sodium can clog inter-aggregate pores, which, in turn, can reduce surface and sub-surface soil hydraulic conductivity and internal drainage and potentially increase surface runoff and erosion [5]. A widely accepted indicator for potential soil-aggregate dispersion is exchangeable sodium percentage (ESP), where typically an ESP ≥ 15% is considered the threshold for initiating soil dispersion in clayey soils with generally low initial hydraulic conductivity [9]. However, Crescimanno et al [11] reported soil degradation occurred at ESPs as low as 2% to 5% in soils with low CECs.…”
Section: Introductionmentioning
confidence: 99%